Differences in the availability of diagnostics and treatment modalities for chronic hepatitis B across Europe. (November 2015) - Ozaras, R.; Corti, G.; Ruta, S.; Lacombe, K.; Mondelli, M.U.; Irwing, W.L.; Puoti, M.; Khalighi, A.; Santos, M.L.; Harxhi, A.; Lazarevic, I.; Soriano, V.; et al.
Abstract: The prevalence and management of chronic hepatitis B virus (HBV) infection differ among European countries. The availability and reimbursement of diagnostics and drugs may also vary, determining distinct treatment outcomes. Herein, we analyse differences in medical facilities for the care of patients with chronic HBV infection across Europe. A survey was sent to the members of the ESCMID Study Group for Viral Hepatitis, all of whom are experts in chronic HBV infection management. The comprehensive survey asked questions regarding hepatitis B surface antigen (HBsAg) prevalence, the availability of diagnostics and drugs marketed, and distinct clinical practice behaviours in the management of chronic HBV infection. World Bank data were used to assess the economic status of the countries. With 16 expert physicians responding (69%), the HBsAg prevalence rates were <1% in France, Hungary, Italy, The Netherlands, Portugal, Spain, and the UK, intermediate (1–5%) in Turkey, Romania, and Serbia, and high (>5%) in Albania and Iran. Regarding the availability and reimbursement of HBV diagnostics (HBV DNA and liver stiffness measurement), HBV drugs (interferon, lamivudine, tenofovir, and entecavir), HBV prophylaxis, and duration of HBeAg-positive and HBeAg-negative HBV infection, the majority of high-income and middle-income countries had no restrictions; Albania, Iran and Serbia had several restrictions in diagnostics and HBV drugs. The countries in the high-income group were also the ones with no restrictions in medical facilities, whereas the upper-middle-income countries had some restrictions. The prevalence of chronic HBV infection is much higher in southern and eastern than in western European countries. Despite the availability of European guidelines, policies for diagnostics and treatment vary significantly across European countries.